Pseudo-Obstruction After Reversal of Ileostomy - Kirsten R. Carlaw; Aizat Drahman; Angelina Di Re (Surgical Techniques Development)
Background: Acute colonic pseudo-obstruction (ACP) is a life-threatening, rare condition of non-mechanical colon dilatation that can result in bowel ischaemia and perforation. The aetiology is relatively unknown but includes older age coupled with high comorbidity, decreased parasympathetic activity, certain medications, chemoradiotherapy and recent surgery. There are limited research data on ACP following reversal of ileostomy after ultra-low anterior resections (ULAR), thus this systematic review included cases from various types of bowel surgeries. Methods: A comprehensive literature search of relevant articles was conducted using the EMBASE, Medline, PubMed, Cochrane, and Scopus databases. Two cases of ACP following ileostomy reversal after ULAR for rectal cancer were also reported from the authors’ rural institution. This systematic review was conducted according to PRISMA 2020 guidelines. Results: A total of 522 studies were screened of which five case reports were included. Two case series (six patients) and the two patients from the authors’ rural institution developed ACP following reversal of ileostomy post-ULAR with potential causes being the > 6 months’ time from initial surgery to reversal causing prolonged colonic mucosal inflammation and reduced wall contractile strength. Anastomotic leak and chemoradiotherapy were other considerations. One of the rural patients developed right colon ischaemia and perforation needing urgent laparotomy, right hemicolectomy and formation of end ileostomy and mucous fistula. Conservative treatment included aperients, enemas, flatus tube, bedside or endoscopic decompression, and neostigmine. Conclusions: Early recognition is vital to treat ACP with medical therapy and decompression to prevent bowel ischaemia and perforation. Further research is needed to better characterise the aetiology, incidence and management strategies for this rare condition.